Who is a Citizen Among Citizens? Public Debates and Draft Laws on the Revision of Romanian Citizenship (1936-1937) - Nicolae DRĂGUȘIN (Eon, 2025)
This paper aims at reconstructing the largely unknown history of the citizenship revision in Romania. Precisely, the paper focuses on the legal initiatives by P. Șeicaru and the Ministry of Justice to regulate through the parliamentary means the revision of citizenship in Romania. The overview of the two draft-laws is made within the context of the discussions in the mainstream press and in the parliamentary debates. Hence, the span of time covered by this in-depth analysis runs between 15 December 1936 and 28 May 1937. This story has a particularly important political significance since it was meant to end up in redefining the boundaries of the sovereign. In this approach, the political participation is conditioned by the ethnical datum and not on the personal will. This contribution is meant to reconstruct the missing part of the history of citizenship revision of Romanian Jews that was accomplished in 1938-1939.